Determination of Phthalates in Marine Sediments Using Ultrasonic Extraction Followed by Dispersive Solid-Phase Extraction and Gas Chromatography–Mass Spectrometry. (22nd June 2021) - Hu, Hongmei; Li, Tiejun; Bao, Jingjiao; Zhang, Xiaoning; Sun, Xiumei; Xu, Kaida; Liu, Qin; Guo, Yuanming
Abstract: A simple, rapid and novel method has been developed and validated for determination of 16 phthalates in marine sediment samples by gas chromatography coupled to mass spectrometry. Freeze dried samples were first ultrasonic extraction by n -hexane:methylene chloride (1:1, v/v) and n -hexane:ethyl acetate (1:1, v/v) and followed by dispersive solid-phase extraction cleanup. The linearity of this method ranged from 1 to 1, 000 μg/L, with regression coefficients ranging between 0.9993 and 0.9999. The limits of detection were in ng/g level, ranging between 0.1 and 0.25 ng/g (dry weight). The concentration of the total phthalates in marine sediment samples from Waters of Dongji (Zhoushan, China), Yueqing Bay (Wenzhou, China) and Coastal Waters of Yuhuan (Taizhou, China) ranged from 235.4 to 608.7 μg/kg with diisobutyl phthalate, dibutyl phthalate and di(2-ethylhexyl) phthalate being the major species, which constitutes of 94.6 and 98.1% of the total phthalates. The recoveries of spiked 16 phthalates at different concentration levels in sediment sample 3 of Waters of Dongji (Zhoushan, China) and sediment sample 3 of Yueqing bay (Wenzhou, China) were in the range of 78–117% and 83–114%, respectively, with relative standard deviations of 2.4–6.8% and 3.4–7.5% ( n = 5), respectively. The performance of the proposed method was also compared with traditional Soxhlet extraction and column chromatography cleanup on the same genuine sediment samples and comparable efficiencies were obtained. It is concluded that this method can be successfully applied for the determination of phthalates in different marine sediment samples.